Ffectiveness of Resistance Exercise and Diabetic Foot SPA Interventions on Fasting Blood Sugar Levels and Peripheral Neuropathy in Type II Diabetes Mellitus Clients - Suid, Nurafni (Syntax Corporation Indonesia, 2023)
Background: Diabetes mellitus is one disease that has a distinctive clinical sign, namely an increase in blood sugar levels beyond the normal range. DM can also cause complications such as peripheral neuropathy. Interventions that can be applied in dealing with the above problems are Resistance exercise and Diabetic Foot Spa. Objective: The purpose of this study was to determine the effectiveness of resistance exercise and diabetic foot spa on fasting blood sugar levels and peripheral neuropathy in Type II Diabetes Mellitus clients. Method: This study is a true experimental research using pre test and post test approach with control group design. Sampling was carried out using a simple random sampling technique and obtained 40 DM patients who sought treatment in the work area of the Srondol Health Center, which were divided into 2 groups (Intervention and Control). Statistical analysis Pre-Test Post-Test difference test using Paired T-Test difference test and Wilcoxon test then Inter-group difference test using Independent T-Test and Mann Whitney U-Test. Results: This study showed that there were significant differences before and after the combination treatment of Resistance exercise and Diabetic Foot Spa on fasting blood sugar levels values (p = 0.000), and peripheral sensory neuropathy responses (p = 0.031), Dorsiflexion (p = 0.003), Plantarflexion (p = 0.011), Inversion (p = 0.000), Eversion (p = 0.018), autonomic neuropathy (p = 0.108), while Resistance exercise and Diabetic Foot Spa did not have significant differences in motor neuropathy response foot deformity (p = 1,000) and autonomic neuropathy (p = 0.108). Conclusion: Resistance exercise and Diabetic foot spa interventions are effective against fasting blood sugar levels and peripheral sensory, motor neuropathy (joint area of motion) in type II diabetes mellitus clients.